SEG Technical Program Expanded Abstracts 2007 2007
DOI: 10.1190/1.2793065
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic velocity changes in seismic time‐lapse data

Abstract: Reservoir production causes subsurface deformations and changes in seismic velocity. These deformations and velocity changes can be monitored using time-lapse seismic data. A fundamental challenge in the interpretation of time shifts observed in time-lapse data is the decomposition of the time delay into a spatial compaction component and a velocity change component. Several authors (Hatchell and Borne, 2005; Janssen et al., 2006) have published the application of pragmatic linear relationships between overbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In practice, lateral variations must imprint upon the trends we predict from anisotropy through equation (33). Our result is consistent with previous work by Herwanger et al (2007) who established through numerical modelling that a decrease with offset could be achieved using an anisotropic velocity variation calibrated by the third-order coefficients on Prioul et al (2004). Here, it is observed that the time-shift gradient is determined predominantly by the first term containing g = (v S /v P ) 2 , and to a lesser degree by the second term containing g and B T /B N .…”
Section: Predictions Of Time-shift Dependence On Incidence Anglesupporting
confidence: 93%
See 1 more Smart Citation
“…In practice, lateral variations must imprint upon the trends we predict from anisotropy through equation (33). Our result is consistent with previous work by Herwanger et al (2007) who established through numerical modelling that a decrease with offset could be achieved using an anisotropic velocity variation calibrated by the third-order coefficients on Prioul et al (2004). Here, it is observed that the time-shift gradient is determined predominantly by the first term containing g = (v S /v P ) 2 , and to a lesser degree by the second term containing g and B T /B N .…”
Section: Predictions Of Time-shift Dependence On Incidence Anglesupporting
confidence: 93%
“…Our result is consistent with previous work by Herwanger et al . () who established through numerical modelling that a decrease with offset could be achieved using an anisotropic velocity variation calibrated by the third‐order coefficients on Prioul et al . ().…”
Section: Offset‐dependent Time‐shiftsmentioning
confidence: 99%
“…The magnitudes of the two-way traveltime shifts shown in Figures 8, 9, 10, and 11 are higher than those typically observed in field data (Guilbot and Smith, 2002;Hatchell and Bourne, 2005;Herwanger et al, 2007;Hodgson et al, 2007;Rickett et al, 2007). Apart from differences due to the use of shot records rather than poststack migrated data, these disagreements may be caused by integration of rock physics and empirical data in the geomechanical modeling.…”
Section: Discussion: Geomechanical Complexity and Magnitude Of Time Smentioning
confidence: 68%
“…Previous research based on geomechanical and seismic methods includes two main directions. One of them focuses on zero-offset time-lapse data governed by vertical stress/strain (Landrø and Stammeijer, 2004;Hatchell and Bourne, 2005;Roste, 2007), while the other considers a full triaxial stress field (Herwanger et al, 2007;Sayers and Schutjens, 2007;Scott, 2007;Herwanger and Horne, 2009;. Whereas the approach based on vertical strain helps evaluate compaction limits, horizontal and shear stress/strain are also induced during production, generating a heterogeneous, anisotropic velocity field inside and around the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, reflectors A, B, and C ( Figure 2) are used to measure time shifts of P-, S-and PS-waves for a range of pressure drops and to evaluate the linearity of the pressure dependence of time shifts. P-wave time shifts in Figure 4 are somewhat larger than typical values measured in the field (Guilbot and Smith, 2002;Hatchell and Bourne, 2005;Herwanger et al, 2007;Hodgson et al, 2007;Rickett et al, 2007;Staples et al, 2007;De Gennaro et al, 2008). Smaller values of the third-order stiffnesses C αβγ , or a decrease in the effective stress coefficient (α) at larger pressure drops will reduce the magnitude of modeled time shifts.…”
Section: Time-shift Trends Versus Reflector Depthmentioning
confidence: 72%